2009
DOI: 10.1097/hjh.0b013e328329e4c0
|View full text |Cite
|
Sign up to set email alerts
|

Implication of chromosome 13 on hypertension and associated disorders in Lyon hypertensive rats

Abstract: Hypertension and associated disorders are major risk factors for cardiovascular disease. The Lyon Hypertensive rat (LH) is a genetically hypertensive strain that exhibits spontaneous and saltsensitive hypertension, exaggerated proteinuria, high body weight, hyperlipidemia and elevated insulin-to-glucose ratio. Previous genetic mapping identified Quantitative Trait Loci (QTL) influencing blood pressure on chromosome 13 (RNO13) in several models of hypertension. To study the effects of a single chromosome on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Gilibert et al 127 confirmed in consomic studies using BN as a reference strain in an LH-13 BN consomic strain, in which BN/ NHsdMcwi-RNO13 was transferred into the LH background, the functional relevance of the RNO13 carrying BP-QTL (Table 2). Interestingly, the LH-13 BN consomic strain exhibits a 50% reduction in proteinuria in LH-13 BN compared with LH.…”
Section: Consomic Studiessupporting
confidence: 51%
See 3 more Smart Citations
“…Gilibert et al 127 confirmed in consomic studies using BN as a reference strain in an LH-13 BN consomic strain, in which BN/ NHsdMcwi-RNO13 was transferred into the LH background, the functional relevance of the RNO13 carrying BP-QTL (Table 2). Interestingly, the LH-13 BN consomic strain exhibits a 50% reduction in proteinuria in LH-13 BN compared with LH.…”
Section: Consomic Studiessupporting
confidence: 51%
“…127 In contrast, reciprocal introgression of LH-RNO13 into the BN background is not capable of inducing a proteinuria phenotype in the consomic strain BN-13 LH . 127 …”
Section: Consomic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This panel is used as a genetic tool to determine chromosomes that harbor genes involved in complex traits [19], and has been used specifically to identify chromosomes involved in hypertension [20-22]. Other panels, such as the Lyon hypertensive (LH) consomic strain (LH-17(BN)) has shown utility for traits involved in metabolic syndrome [23].…”
Section: Introductionmentioning
confidence: 99%